Copper-containing grain-oriented silicon steel and its manufacturing method
Optimized chemical compositions and manufacturing processes for copper-containing directional silicon steel enhance magnetic characteristics, achieving low iron loss and high flux density, addressing the limitations of existing methods.
Patent Information
- Application Number
- JP2024540896
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-12
- Filing Date
- 2023-01-12
- Publication Date
- 2025-02-04
AI Technical Summary
Existing methods for manufacturing directional silicon steel struggle to achieve low iron loss and high magnetic flux density while maintaining cost-effectiveness and environmental sustainability, particularly in controlling inhibitor distribution and temperature adjustments during the manufacturing process.
A copper-containing directional silicon steel with specific chemical compositions and optimized manufacturing processes, including controlled heating temperatures, two-step annealing, and precise inhibitor ratios, to enhance magnetic characteristics.
The solution results in a copper-containing directional silicon steel with iron loss below 0.85 W/kg and magnetic flux density exceeding 1.90 T, demonstrating improved magnetic properties and applicability.
Smart Images

Figure 2025503613000001 
Figure 2025503613000002 
Figure 2025503613000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to metallic materials and methods for manufacturing the same, and more particularly to grain-oriented silicon steel and methods for manufacturing the same. [Background technology]
[0002] In recent years, against the backdrop of energy saving and emission reduction, the demand for grain-oriented electrical steel with higher magnetic flux density and thinner gauge has increased significantly in many fields, such as ultra-high voltage (UHV) projects, high-speed railways and rail transit, subway construction, photovoltaic power generation, real estate, and new energy vehicle charging piles. Based on this demand, grain-oriented silicon steel is being developed with the aim of low cost, low core loss, and environmental friendliness.
[0003] In the prior art, the conventional manufacturing method of grain-oriented silicon steel can be divided into two manufacturing processes based on the heating temperature of hot rolling. One is a high-temperature process in which the heating temperature of the slab is 1250°C to 1320°C and inhibitors such as AlN and Cu are used. The other is a low-temperature process in which the heating temperature of the slab is 1100°C to 1250°C and inhibitors such as AlN and CuS are used, and the process requires nitriding after decarburization to form an acquired inhibitor to obtain the inhibitory ability. The low-temperature process is known as the current mainstream manufacturing process of grain-oriented silicon steel due to its advantages such as low energy consumption and high yield.
[0004] In recent years, various technical means for optimizing the design have been adopted to improve the magnetic properties of grain-oriented silicon steel products. For example, a Chinese application entitled "Manufacturing Method for Improving Electromagnetic Properties of Grain-oriented Silicon Steel" (Publication No. CN103834908A, Publication Date June 4, 2014) discloses a manufacturing method for improving the electromagnetic properties of grain-oriented silicon steel. This disclosure obtains high magnetic flux density grain-oriented silicon steel by controlling the amount of nitrogen intrusion according to the proportion of 30-100 nm AlN precipitates in a normalized steel sheet. However, this disclosure is mainly directed to an inhibitor component system mainly composed of AlN.
[0005] As another example, a Chinese application entitled "Method for Producing Low-Temperature High Flux Density Thin-Gauge Grain-Oriented Silicon Steel Strip" (Publication No. CN110055393A, Publication Date July 26, 2019) discloses a method for producing low-temperature high flux density thin-gauge grain-oriented silicon steel strip. The disclosure optimizes the properties of thin-gauge grain-oriented silicon steel by adjusting the soaking temperature of decarburization annealing and the nitriding process according to the change in raw material composition and the final rolling temperature of hot rolling. However, in this technical solution, both on-site decarburization and nitriding are performed on the production line of the decarburization annealing equipment, so that the decarburization and nitriding temperatures need to be adjusted simultaneously, which makes on-site control extremely difficult.
[0006] As another example, a Chinese application entitled "High magnetic flux density grain-oriented silicon steel containing composite inhibitor and its manufacturing method" (Publication No. CN112522609A, published on March 19, 2021) discloses that the addition of Cu can effectively prevent the primary grain size from becoming excessively large, and the MgSO4 added to the magnesium oxide additive forms an acquired inhibitor together with Cu to form a dual inhibitor system, thereby avoiding the generation of a large amount of N2 during high-temperature annealing and ensuring the stability of magnetic properties. However, since this technical solution adds an inhibitor to magnesium oxide, the problem of non-uniform distribution of the inhibitor remains.
[0007] In the prior art, the addition of alloying elements is the most common method to improve the magnetic properties of grain-oriented silicon steel products. As disclosed in pages 491 and 505 of "Principles of Material Science of Electrical Steel" (Higher Education Press), adding 0.45% Cu can reduce the heating temperature to 1250-1280°C, but the magnetic properties of the steel products are below 1.88T, and the content of Cu added in the above low-temperature process is generally controlled to 0.01-0.1%. Therefore, how to improve the magnetic properties of copper-containing grain-oriented silicon steel is still a technical problem that needs to be urgently solved. Summary of the Invention [Problem to be solved by the invention]
[0008] The purpose of this disclosure is to 17 / 50 The present invention provides a copper-containing grain-oriented silicon steel having a magnetic flux density B8 of less than 0.85W / Kg and a magnetic flux density B8 of more than 1.90T, which has excellent magnetic properties, good prospects for popularization, and good application value. [Means for solving the problem]
[0009] In order to achieve the above object, the present disclosure provides a ferroelectric liquid crystal display comprising 90 wt% or more Fe and unavoidable impurities, as well as the following chemical elements in mass percentages: C: 0.04-0.09%, Si: 2.9-4.0%, Mn: 0.05-0.2%, S: 0.005-0.01%, soluble aluminum (Als): 0.015-0.035%, N: 0.0010-0.01%, Sn: 0.01-0.1%, and Cu, Provided is a copper-containing grain-oriented silicon steel that satisfies 3%≦Si+Cu≦4.4%, 0.05≦Cu / Si≦0.13, and 24≦(Mn+Cu) / S≦118.
[0010] Preferably, the present disclosure comprises the following chemical elements in mass percentages: The alloy contains C: 0.04-0.09%, Si: 2.9-4.0%, Mn: 0.05-0.2%, S: 0.005-0.01%, soluble aluminum (Als): 0.015-0.035%, N: 0.0010-0.01%, Sn: 0.01-0.1%, and Cu, with the balance being Fe and unavoidable impurities, and the Cu content is The present invention provides a copper-containing grain-oriented silicon steel that satisfies 3%≦Si+Cu≦4.4%, 0.05≦Cu / Si≦0.13, and 24≦(Mn+Cu) / S≦118.
[0011] In the copper-containing grain-oriented silicon steel according to the present disclosure, the design principles of each chemical element are as follows:
[0012] C: C can form γ-phase during hot rolling. However, if the C content in the steel is less than 0.04%, effective γ-phase cannot be formed, and if the C content in the steel is more than 0.09%, decarburization becomes difficult. Therefore, in the copper-containing grain-oriented silicon steel according to the present disclosure, the mass percentage of C is controlled to 0.04% to 0.09%.
[0013] Si: The Si element can effectively increase the resistivity of the material and reduce the iron loss of the steel. However, the higher the Si content in the steel, the worse the manufacturability. If the Si content in the steel exceeds 4.0%, the cold rolled strip fracture rate increases, and if the Si content in the steel is less than 2.9%, the effect of effectively reducing the iron loss and improving the properties cannot be achieved. Therefore, in the copper-containing grain-oriented silicon steel according to the present disclosure, the mass percentage of Si is controlled to 2.9% to 4.0%, preferably 3.1% to 3.5%.
[0014] Mn: The effect of Mn is similar to that of Si. Mn can also improve the resistivity of the material and reduce the iron loss of the steel. In addition, Mn can combine with S to form MnS, which is an inhibitor. If the Mn content in the steel is less than 0.05%, the above effect cannot be achieved. However, if the Mn content in the steel exceeds 0.2%, the formed MnS becomes coarse, which leads to a deterioration in the hot rolling workability and magnetic properties of the steel. Therefore, in the copper-containing grain-oriented silicon steel according to the present disclosure, the mass percentage of Mn is controlled to 0.05% to 0.2%, preferably 0.065% to 0.15%.
[0015] S: S mainly combines with Mn, Cu, etc. to form MnS or CuS, which are inhibitors. If the S content in the steel is less than 0.005%, the above effects cannot be effectively achieved. If the S content in the steel exceeds 0.01%, refining and desulfurization become difficult. Therefore, in the copper-containing grain-oriented silicon steel according to the present disclosure, the mass percentage of S is controlled to 0.005% to 0.01%.
[0016] Soluble aluminum (Als): Als mainly forms AlN inhibitor together with N. If the Als content in the steel exceeds 0.035%, the quality of the lower layer will deteriorate. If the Als content in the steel is less than 0.015%, the inhibitor effect cannot be achieved. Therefore, in the copper-containing grain-oriented silicon steel according to the present disclosure, the Als content is controlled to 0.015% to 0.035%.
[0017] N: N can form an AlN inhibitor together with Als. If the N content in the steel is less than 0.0010%, the inhibitor is insufficient. If the N content in the steel exceeds 0.01%, the molten steel is likely to swell during steelmaking and casting, and defects such as peeling and blistering may occur in the product. Therefore, in the copper-containing grain-oriented silicon steel according to the present disclosure, the N content is controlled to 0.0010% to 0.01%.
[0018] Sn: Sn belongs to the grain boundary segregation element and is involved in segregation and inhibition, so that it can further improve the inhibition ability. However, it should be noted that if the Sn content in the steel exceeds 0.1%, it becomes difficult to control the lower layer, and if the Sn content in the steel is less than 0.01%, the effect of segregation and inhibition cannot be achieved. Therefore, in the copper-containing grain-oriented silicon steel according to the present disclosure, the Sn content is controlled to 0.01% to 0.1%, preferably 0.05% to 0.1%.
[0019] Cu: Cu can increase resistivity and reduce iron loss. Meanwhile, Cu, like Si, is an austenite stabilizing element. If the Cu content in the steel is too low, the beneficial effects described above cannot be achieved. If the Cu content in the steel is too high, the rolling becomes more difficult, the band break rate becomes higher, and the control of the lower layer becomes difficult, like the above-mentioned Si. Therefore, in the copper-containing grain-oriented silicon steel according to the present disclosure, the Cu content must satisfy the following relationships: 3%≦Si+Cu≦4.4%, 0.05≦Cu / Si≦0.13, and 24≦(Mn+Cu) / S≦118. In this case, Cu and Mn can react with S to produce CuS and MnS, which act as inhibitors. By controlling the Cu content so as to satisfy the above specific relationships, the beneficial effects of Cu, which improves the magnetic properties of the steel, can be fully exerted.
[0020] Preferably, the Cu content satisfies 3.3%≦Si+Cu≦4.1%, and more preferably 3.8%≦Si+Cu≦4.1%.
[0021] Preferably, the Cu content satisfies 24≦(Mn+Cu) / S≦111, and more preferably 69≦(Mn+Cu) / S≦111.
[0022] Preferably, the Cu content satisfies 0.19%≦Cu≦0.44%, more preferably 0.27%≦Cu≦0.44%. Preferably, the copper-containing grain-oriented silicon steel according to the present disclosure has a thickness of 0.23 mm or less.
[0023] Preferably, the copper-containing grain-oriented silicon steel according to the present disclosure has an iron loss P 17 / 50 is less than 0.85 W / Kg, more preferably 0.78 W / Kg or less, and the magnetic flux density B8 exceeds 1.90 T.
[0024] Preferably, the copper-containing grain-oriented silicon steel according to the present disclosure has a secondary recrystallized average grain size of 10 to 20 mm, more preferably 12 to 16 mm, and an average grain size deviation of less than 5 mm, more preferably 4 mm or less.
[0025] In another aspect, there is provided a method for producing the above-mentioned copper-containing grain-oriented electrical steel, comprising the steps of: (1) The process of smelting and casting molten steel to prepare slabs; (2) subjecting the slab to hot rolling to prepare a hot rolled steel sheet; (3) subjecting the steel sheet to two-stage normalizing annealing, comprising performing a first stage annealing at a temperature of 1100-1150°C for 60-120 seconds, performing a second stage annealing at a temperature of 900-950°C for 60-120 seconds, and then water cooling, at which the cooling rate is controlled to 30°C / sec or more, so that the volume ratio of the total amount of AlN, CuS and MnS precipitates having sizes of 30-100 nm to the total amount of precipitates in the steel sheet after the normalizing annealing is 30-80%; (4) Cold rolling process; (5) Decarburization annealing process; (6) Nitriding process; (7) applying a high temperature insulating agent; (8) high-temperature annealing process; and (9) A process of applying an insulating film and hot flattening annealing It is also an object of the present disclosure to provide a method comprising:
[0026] The method according to the present disclosure can be realized by modifying the original production line, which is simple and feasible, and can effectively improve the level of magnetic properties of copper-containing grain-oriented silicon steel. The copper-containing grain-oriented silicon steel prepared by the present method has a low iron loss P 17 / 50 It has excellent magnetic properties because its magnetic flux density B8 is more than 1.90T and its electrical resistance is less than 0.85W / Kg.
[0027] Through much research, the inventors of the present disclosure have found that by optimizing the design of a manufacturing method for copper-containing grain-oriented silicon steel based on a rational chemical composition design of the copper-containing grain-oriented silicon steel, it is possible to effectively improve the magnetic properties of copper-containing grain-oriented silicon steel products.
[0028] It should be noted that it is very important to control the inhibitors in the manufacturing process of copper-bearing grain-oriented silicon steel. Research has shown that after normalizing annealing, precipitates smaller than 30 nm will dissolve and decompose into solid solution in the subsequent manufacturing process, while precipitates larger than 100 nm will not function as inhibitors.
[0029] In the method according to the present disclosure, by using two-stage normalizing annealing in step (3) and setting the process parameters of normalizing annealing within the above ranges, the volume ratio of the total amount of AlN, CuS and MnS precipitates having a size of 30 to 100 nm to the total amount of precipitates in the steel sheet after normalizing annealing can be controlled to 30 to 80%. If this volume ratio is less than 30%, the suppression ability becomes insufficient, and the magnetic properties of the final product become poor. If the volume ratio exceeds 80%, the suppression ability becomes too strong, and it is similarly difficult to obtain excellent magnetic properties.
[0030] Preferably, in step (4) of the method of the present disclosure, the cold rolling reduction is 88-92%. Different cold rolling reductions result in different dislocation densities and differences in accumulated dislocation energy after cold rolling, which results in different driving effects on the primary recrystallization process. If the cold rolling reduction is less than 88%, the driving force for primary recrystallized grain growth is insufficient. If the cold rolling reduction is more than 92%, the driving force for primary recrystallized grain growth is too strong. In either case, it is difficult to obtain a good primary recrystallized grain size.
[0031] Preferably, in step (5) of the method according to the present disclosure, the decarburization annealing temperature T=804.5+56.5×A+6.2×B, where A represents the volume ratio of the total amount of AlN, CuS and MnS precipitates of 30-100 nm to the total amount of precipitates in the steel sheet after normalizing annealing, and B represents the cold rolling reduction. By setting the decarburization annealing temperature so as to satisfy the above relationship, it is possible to satisfy the suppression ability and obtain a good secondary recrystallized structure.
[0032] Preferably, in step (6) of the method according to the present disclosure, the steel has a nitrogen content after nitriding of 200 to 300 ppm, in which case the suppression ability can be satisfied and a better secondary recrystallized structure can be obtained.
[0033] Preferably, in step (7) of the method according to the present disclosure, the high temperature insulating agent applied is MgO.
[0034] Preferably, in step (2) of the method according to the present disclosure, the heating temperature is controlled to 1050 to 1150°C.
[0035] Preferably, in step (2) of the method according to the present disclosure, the thickness of the hot-rolled steel sheet is controlled to be 1.5 to 2.9 mm.
[0036] Preferably, in step (8) of the method of the present disclosure, the temperature is first raised to 500 to 700°C and held there, then continuously raised to 700 to 1050°C in an annealing atmosphere of dry N2+H2 mixed gas with a volume ratio of 50% or more, then continuously raised to 1050 to 1150°C in an annealing atmosphere of dry N2+H2 mixed gas with a volume ratio of less than 50%, and finally continuously raised to 1150 to 1200°C in an annealing atmosphere of pure H2.
[0037] Preferably, in step (9) of the method of the present disclosure, the insulating coating may be a conventional insulating coating material for grain-oriented silicon steel, such as an insulating coating made of phosphate, silicon dioxide, and chromic anhydride.
[0038] Preferably, in step (6) of the method according to the present disclosure, when the temperature is increased to 500 to 700° C., the holding time is 20 hours or longer.
[0039] Compared with the prior art, the copper-containing grain-oriented electrical steel and its manufacturing method according to the present disclosure have the following advantages and beneficial effects: Compared with the prior art, the present disclosure provides a copper-containing grain-oriented silicon steel product with good magnetic properties by rationally designing the chemical composition of the copper-containing grain-oriented silicon steel and optimizing various process parameters in the manufacturing method, such as controlling the volume ratio of the total amount of AlN, CuS and MnS precipitates having a size of 30-100 nm to the total amount of precipitates in the normalized steel sheet, the cold rolling reduction, the decarburization temperature, the amount of nitriding, and the decarburization annealing. The magnetic properties of the prepared copper-containing grain-oriented silicon steel are improved by at least 1 / 2 grade.
[0040] The method for producing the copper-containing grain-oriented silicon steel according to the present disclosure is simple and feasible. The copper-containing grain-oriented silicon steel prepared by the present manufacturing method has a low core loss P 17 / 50 The magnetic flux density B8 is less than 0.85W / Kg, and the magnetic flux density B8 is more than 1.90T, which has good prospects for popularization and application value. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0041] The copper-containing grain-oriented electrical steel and the manufacturing method thereof according to the present disclosure will be further described and illustrated with reference to specific examples below. However, the description and illustration should not be construed as unduly limiting the technical solutions of the present disclosure.
[0042] Examples 1 to 9 and Comparative Examples 1 to 9 Table 1 shows the mass percentages of the chemical elements in the copper-containing grain-oriented silicon steels of Examples 1 to 9 and the grain-oriented silicon steels of Comparative Examples 1 to 9.
[0043] [Table 1]
[0044] The copper-containing grain-oriented silicon steels of Examples 1 to 9 according to the present disclosure were prepared by the following process. (1) A process of smelting and casting in accordance with the chemical composition shown in Table 1. (2) Hot rolling process: The heating temperature is controlled to 1050 to 1150°C, and rolling is performed to control the thickness of the hot-rolled sheet to 1.5 to 2.9 mm. (3) Two-stage normalizing annealing process: a first stage annealing is performed at a temperature of 1100-1150°C and held for 60-120 seconds, a second stage annealing is performed at a temperature of 900-950°C and held for 60-120 seconds, and then water cooling is performed, in which the cooling rate is controlled to 30°C / sec or more, so that the volume ratio of the total amount of AlN, CuS and MnS precipitates having a size of 30-100 nm to the total amount of precipitates in the steel sheet after normalizing annealing is 30-80%. (4) Cold rolling process: The cold rolling reduction is controlled to 88 to 92%. (5) Decarburization annealing process: The decarburization temperature is controlled to T = 804.5 + 56.5 × A + 6.2 × B, where A represents the volume ratio of the total amount of AlN, CuS and MnS precipitates of 30 to 100 nm to the total amount of precipitates after normalizing, and B represents the cold rolling reduction. (6) Nitriding process: The nitrogen content of the steel sheet after nitriding is controlled to 200 to 300 ppm. (7) A process of applying a high-temperature insulating agent. MgO was used as the high-temperature insulating agent. (8) High-temperature annealing process: First, the temperature was raised to 500-700°C and held for 20 hours or more, then the temperature was continuously raised to 700-1050°C in an annealing atmosphere of dry N2+H2 mixed gas with a volume ratio of 50% or more, then the temperature was continuously raised to 1050-1150°C in an annealing atmosphere of dry N2+H2 mixed gas with a volume ratio of less than 50%, and finally the temperature was continuously raised to 1150-1200°C in an annealing atmosphere of pure H2. (9) A process of applying an insulating coating and performing hot smoothing annealing. The insulating coating is made of phosphate, silicon dioxide, and chromic anhydride.
[0045] The copper-containing grain-oriented electrical steels of Examples 1 to 9 according to the present disclosure were prepared by a method including the above steps, and their chemical compositions and related process parameters met the control requirements of the design specifications of the present disclosure.
[0046] The comparative steels of Comparative Examples 1-9 were prepared by the same method as Example 1 of the present disclosure, except that at least one of their chemical compositions and / or process parameters did not meet the requirements of the present disclosure.
[0047] Tables 2-1 and 2-2 summarize specific process parameters for the copper-containing grain-oriented silicon steels of Examples 1 to 9 and the grain-oriented silicon steels of Comparative Examples 1 to 9 in the process flow of the above-mentioned manufacturing method.
[0048] [Table 2-1]
[0049] [Table 2-2]
[0050] After the two-stage normalizing annealing of the above step (3) was completed in Examples 1 to 9 and Comparative Examples 1 to 9 according to the process parameters shown in Table 2, the steel sheets after normalizing annealing in the Examples and Comparative Examples were sampled, observed, and analyzed. The specific operation was as follows.
[0051] 1) The steel plate was sampled to a size of 15mm x 15mm, and the precipitates in the normalized steel plate were extracted using the carbon film extraction replica method. In this method, electrolytic corrosion was performed in a constant current mode of 0.5mA in an electrolytic system of 89% methanol + 10% acetylacetonate + 1% tetramethylammonium chloride; after electrolytic corrosion was completed, the sample was washed with absolute ethanol, and then the washed sample was blow-dried; carbon was sprayed onto the treated sample using a vacuum spray device; the sample after carbon spraying was connected to an electrode, and electrolysis was performed at a voltage of 12V using 7% perchloric acid ethanol; after the carbon film fell off the sample, the carbon film was immersed in a 1% hydrochloric acid ethanol solution, then in absolute ethanol, and finally in deionized water, and the carbon film was removed using a nickel mesh, and the carbon film was placed on a filter paper and dried for later use.
[0052] 2) The composition and size of precipitates in the normalized steel sheets were observed using a transmission electron microscope (model: JEM2100, JEOL) and a supporting energy dispersive spectrometer (model: IE250, Oxford Instruments plc, UK). It was found that precipitates of AlN, CuS and MnS were present in all the steel sheets of the examples and comparative examples. For each sample, 200 fields of view were continuously photographed at a magnification of 30,000 times. The number and size of precipitates in the photographed fields of view were counted using the image analysis software Image-Pro Plus. The volume ratio of the total amount of AlN, CuS and MnS precipitates having a size of 30 to 100 nm to the total amount of precipitates was calculated. In all examples, the calculation was performed according to the following method.
number
[0053] The calculation results are summarized in Table 3 below.
[0054] Table 3 shows the results of observation and analysis of the steel sheets after normalizing annealing in the examples and comparative examples.
[0055] [Table 3]
[0056] The copper-containing grain-oriented silicon steels of Examples 1 to 9 and the grain-oriented silicon steels of Comparative Examples 1 to 9 were sampled separately, and the magnetic flux density B8, core loss P 17 / 50 The results of the tests are summarized in Table 4 below.
[0057] The above-mentioned relevant properties were measured by the following methods. Magnetic flux density B8 and iron loss P 17 / 50 : Magnetic flux density B8 and iron loss P of the examples and comparative examples 17 / 50 was measured according to GB / T13789.
[0058] Secondary recrystallized average grain size and average grain size deviation: The secondary recrystallized average grain size and average grain size deviation of the examples and comparative examples were measured by an intercept method in accordance with the metal average grain size measurement method of GB / T6394-2017.
[0059] Table 4 shows the test results of the properties of the copper-containing grain-oriented silicon steels of Examples 1 to 9 and the grain-oriented silicon steels of Comparative Examples 1 to 9.
[0060] [Table 4]
[0061] As shown in Table 4, compared with Comparative Examples 1 to 9, the copper-containing grain-oriented silicon steels of Examples 1 to 9 had a lower iron loss P 17 / 50 is low, magnetic flux density B8 is high, and iron loss P 17 / 50 The copper-containing grain-oriented silicon steels of Examples 1 to 9 have better magnetic properties because the average grain size of secondary recrystallized grains is 10 to 16 mm and the average grain size deviation is 1.2 mm to 4 mm.
[0062] As can be seen from the combination of Tables 1 to 4 above, the grain-oriented silicon steels of Comparative Examples 1 to 9 have poor magnetic properties because the Cu contents of Comparative Examples 1 and 2 exceed the design range of the present disclosure, but the copper-containing grain-oriented silicon steels of Examples 1 to 9, which satisfy the design requirements of the present disclosure, have significantly better magnetic properties.
[0063] The designed chemical element composition of Comparative Example 3 is exactly the same as that of Example 2. However, Comparative Example 3 does not employ the technical parameters of the two-step normalizing annealing treatment that meets the requirements of the present disclosure. Therefore, the volume ratio of the total amount of AlN, CuS and MnS precipitates having sizes of 30 to 100 nm to the total amount of precipitates in the steel sheet after normalizing annealing exceeds the design range of the present disclosure. As a result, the magnetic properties of the grain-oriented silicon steel finally obtained in Comparative Example 3 are deteriorated.
[0064] The designed chemical element compositions of Comparative Examples 4 and 5 are exactly the same as those of Example 3. However, the cold rolling reduction ratios in the cold rolling stage of step (4) of Comparative Examples 4 and 5 exceed the design range of the present disclosure, and therefore the magnetic properties of the grain-oriented silicon steels finally obtained in Comparative Examples 4 and 5 are deteriorated.
[0065] The designed chemical element compositions of Comparative Examples 6 and 7 are exactly the same as those of Example 4. However, the decarburization temperatures in the decarburization annealing step of step (5) of Comparative Examples 6 and 7 do not satisfy the design requirements of the present disclosure, and therefore the magnetic properties of the grain-oriented silicon steels finally obtained in Comparative Examples 6 and 7 are poor.
[0066] The designed chemical element compositions of Comparative Examples 8 and 9 are exactly the same as those of Example 5. However, the nitrogen content of the steel sheets after nitriding in step (5) of Comparative Examples 8 and 9 exceeds the design range of the present disclosure, and therefore the magnetic properties of the grain-oriented silicon steels finally obtained in Comparative Examples 8 and 9 are poor.
[0067] In conclusion, compared with Comparative Examples 1 to 9, Examples 1 to 9 having the designed chemical element composition and employing the manufacturing process of the present disclosure have iron loss P 17 / 50The magnetic flux densities B8, B9, and B10 of the copper-containing grain-oriented silicon steel products are all less than 0.85W / Kg and more than 1.90T, respectively, and the copper-containing grain-oriented silicon steel products have better magnetic properties. Therefore, the copper-containing grain-oriented silicon steel products obtained have good popular prospects and application value.
[0068] It should be noted that the prior art part within the scope of protection of the present disclosure is not limited to the embodiments described in the present specification. All prior art that does not contradict the scheme of the present disclosure, including but not limited to prior patent documents, prior publications, prior publicly known uses, etc., is included in the scope of protection of the present disclosure. Furthermore, the combination of features in the present disclosure is not limited to the combinations described in the claims or specific embodiments. All features described in the present disclosure can be freely combined and may be combined in any way as long as they are not inconsistent with each other.
[0069] It should also be noted that the above-listed embodiments are merely specific examples of the present disclosure. It is clear that the present disclosure is not limited to the above-mentioned embodiments, and all similar variations or modifications that can be directly derived or easily conceived by a person skilled in the art from the contents of the present disclosure should be included within the protection scope of the present disclosure.
Claims
1. In addition to 90 wt. % or more of Fe and unavoidable impurities, the following chemical elements are present in mass percentages: C: 0.04 to 0.09%, Si: 2.9 to 4.0%, Mn: 0.05 to 0.2%, S: 0.005 to 0.01%, Als: 0.015 to 0.035%, N: 0.0010 to 0.01%, Sn: 0.01 to 0.1%, and Cu, wherein the Cu content is A copper-containing grain-oriented silicon steel satisfying 3%≦Si+Cu≦4.4%, 0.05≦Cu / Si≦0.13, and 24≦(Mn+Cu) / S≦118.
2. The copper-containing grain-oriented silicon steel contains the following chemical elements by mass percentage: C: 0.04-0.09%, Si: 2.9-4.0%, Mn: 0.05-0.2%, S: 0.005-0.01%, Als: 0.015-0.035%, N: 0.0010-0.01%, Sn: 0.01-0.1%, and Cu, with the balance being Fe and other unavoidable impurities, and the Cu content is 2. The copper-containing grain-oriented silicon steel according to claim 1, wherein 3%≦Si+Cu≦4.4%, 0.05≦Cu / Si≦0.13, and 24≦(Mn+Cu) / S≦118.
3. The Si content is preferably 3.1 to 3.5%, the Mn content is preferably 0.065 to 0.15%, the Sn content is preferably 0.05 to 0.1%, the Cu content is preferably 0.19 to 0.44%, more preferably 0.27 to 0.44%, and the Cu content is preferably 3.3%≦Si+Cu≦4.1% and / or 24≦(Mn+Cu) / S≦111.
4. The copper-containing grain-oriented electrical steel according to any one of claims 1 to 3, wherein the copper-containing grain-oriented electrical steel has a thickness of 0.23 mm or less.
5. The copper-containing grain-oriented silicon steel according to any one of claims 1 to 4, wherein the copper-containing grain-oriented silicon steel has a secondary recrystallized average grain size of 10 to 20 mm, more preferably 12 to 16 mm, and an average grain size deviation of less than 5 mm, more preferably 4 mm or less.
6. The above copper-containing grain-oriented silicon steel has an iron loss P 17/50 is less than 0.85 W / Kg, more preferably 0.78 W / Kg or less, and the magnetic flux density B 8 The copper-containing grain-oriented electrical steel according to any one of claims 1 to 5, wherein the grain size is greater than 1.90T.
7. A method for producing the copper-containing grain-oriented silicon steel according to any one of claims 1 to 6, (1) A process of smelting and casting molten steel to prepare slabs; (2) subjecting the slab to hot rolling to prepare a hot rolled steel sheet; (3) subjecting the steel sheet to two-stage normalizing annealing, comprising performing a first stage annealing at a temperature of 1100 to 1150°C for 60 to 120 seconds, performing a second stage annealing at a temperature of 900 to 950°C for 60 to 120 seconds, and then water cooling at a cooling rate of 30°C / sec or more, so that the volume ratio of the total amount of AlN, CuS and MnS precipitates having a size of 30 to 100 nm to the total amount of precipitates in the steel sheet after the normalizing annealing is 30 to 80%; (4) cold rolling process; (5) Decarburization annealing step; (6) nitriding step; (7) applying a high temperature isolation agent; (8) a high-temperature annealing step; and (9) A process of applying an insulating film and performing hot flattening annealing The method includes:
8. The method according to claim 7, wherein in step (2), the heating temperature is preferably 1050 to 1150°C, and / or the hot-rolled steel sheet has a thickness of 1.5 to 2.9 mm, and in step (4), the cold-rolling reduction is preferably 88 to 92%, and / or in step (6), the nitrogen content of the steel sheet after nitriding is preferably 200 to 300 ppm.
9. The method according to claim 7 or 8, wherein in the step (5), the decarburization annealing temperature T=804.5+56.5×A+6.2×B, in which A represents a volume ratio of a total amount of AlN, CuS and MnS precipitates having a size of 30 to 100 nm to a total amount of precipitates in the steel sheet after the normalizing annealing, and B represents a cold rolling reduction.
10. In step (8), the temperature is first raised to 500 to 700° C. and maintained for preferably 20 hours or more. Then, a volume ratio of 50% or more of dry N 2 +H 2 The temperature is continuously increased to 700 to 1050°C in an annealing atmosphere of mixed gas, and then dried N 2 +H 2 The temperature is continuously increased to 1050-1150°C in an annealing atmosphere of mixed gas, and finally, pure H 2 The method according to any one of claims 7 to 9, wherein the temperature is continuously increased to 1150 to 1200 ° C. in an annealing atmosphere.
Citation Information
Patent Citations
High-magnetic-induction oriented silicon steel prepared through thin slab continuous casting and rolling and preparation method thereof
CN103774042A
Method for producing thin-gauge low-temperature high-magnetic induction oriented silicon steel strip
CN110055393A
Orientating silicon steel, manufacturing process and equipment
CN1796587A
Production of grain-oriented silicon steel sheet having superior magnetic property
JP1992187721A
Production of grain oriented electrical steel sheet having excellent magnetic characteristic
JP1995252532A